Globalisation is good for you: Distributional effects of mergers caused by globalisation - Pia Weiss; Klaus Wälde (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2001)
Globalisation (in the sense of increased international trade) is usually associated with gains from trade but also distributional effects where e.g. capital owners gain and workers lose, both in real terms. In recent years, globalisation seems to be synonymous to international mergers of firms. This paper shows in a model with Cournot competition that international mergers due to globalisation also imply gains from trade. Under plausible assumptions for capital intensities and in contrast to the usual results, however, both capital owners and workers gain in real terms. This effect is due to the reduction in the consumption good price caused by an increase in competition.
Keywords: 330; Multinationales Unternehmen; Fusion; Globalisierung; Internationale Arbeitsteilung; Duopol; Außenhandelseffekt; Wohlfahrtseffekt; Funktionelle Einkommensverteilung; Konsumentenrente; Theorie